PO8 Bioprospecting of Macromycete Fungi: Advances in the Knowledge of Their Chemistry - Chegwin Angarita, Carolina (Revista Productos Naturales, 2025)
Macromycete fungi constitute a kingdom with an estimated 2.2 to 3.8 million species, most of which remain largely unknown—not only in terms of mycological inventory but also regarding their chemical composition and potential for bioprospecting. In our country, approximately 300,000 species are estimated to exist, yet only 2.5% have been identified. This talk will present the advances made by the Macromycete Fungi Chemistry Research Group in studying native fungi and foreign strains, highlighting their applications in health, well-being, the environment, cosmetics, the agricultural industry, and nanotechnology.
Keywords: Biotechnology; Bioremediation; Mushrooms; Mushroom culture